Level of satisfaction on Socio- Economic Condition of Occupation changed Dalit Caste in Kaski - Palikhe, Amin; Bhandari, Hari Bahadur; Adhikari, Nabin Bahadur; Subedi, Netra Prasad (Kanya Journal, 2022)
With reference to the title “Level of satisfaction on Socio- Economic Condition of Occupation changed Employee in Dalit Caste in Kaski” has main purpose of the study to explore the socio-economic condition and their satisfaction level in Dalit community in Kaski. This study uses descriptive cum analytical research design with 300 sample taken from rural and urban area from Nepali, Bishwokarma and Pariyar caste. The purposive and stratified sampling was used as multi stage sampling system. Standard set of questionnaire was used to collect the data from primary sources and inferential statistics chi-square test was used to show the level of satisfaction. Data processing of the study used SPSSS program. Level of satisfaction of occupation changed Dalit was average where there is significance association between occupation changed with overall satisfaction level but no occupational changed Dalit caste has no significant association with overall satisfaction at 5 % level of significant. It is highly recommended to make suitable policy by government that Dalit can change their occupation according to change in environment in Dalit caste to get high level of satisfaction from change in socio-economic situation.